Virgin Coconut Oil as a New Concept for Periodontal Tissue Regeneration via Expressions of TNF-α and TGF-β1 - Hasanuddin Thahir; Arni Irawaty Djais; Mansjur Nasir; Ayu Rahayu Feblina; Afdalia Annisa; Nir Etriyani; Harun Achmad (International Journal of Biomaterials)
Background. Virgin coconut oil is a natural product from coconut that has many benefits such as antibacterial, anti-inflammatory, and antioxidant. Inflammatory disease of the periodontal tissues has a high prevalence worldwide. The main etiology of periodontitis plaque of biofilm contains colonies of pathogenic microorganisms. The occurrence of inflammation in the periodontal tissue stimulates the release of inflammatory mediators, such as TNF-α and TGF-β. Treatment for periodontitis can be performed starting from initial therapy and usually accompanied by additional therapy such as local drug delivery. VCO can be used as an alternative to antibiotics. Objective. To determine the effectiveness of VCO gel on periodontal tissue regeneration materials through the expression of TNF-α and TGF-β1. Methods. This is an experimental laboratory with a posttest-only control group design. VCO was made from grated fresh coconut and then mixed with NaCMC to obtain gel viscosity. The subjects of this study were 30 male periodontitis-induced Wistar rats by injecting Porphyromonas gingivalis into the gingival sulcus. Wistar rats were then divided into 3 groups. On the 7th and 14th days, the rats were sacrificed and the jaw was sampled to determine the amount of TNF-α and TGF-β1 expression in the regenerative process of periodontal tissue. Result. The amount of TNF-α and TGF-β1 increased significantly in the treatment group, but not as much as the increase in the positive control and negative control groups. Conclusion. VCO gel can affect the expression of TNF-α and TGF-β1 in the regeneration process of periodontal tissue in periodontitis-induced rats.